(untitled) (Fiep Bulletin - online, 2013)
Colégio Sion is a traditional educational institution rendering services in the city of Rio de Janeiro and other Brazilian cities. Education, as example of what the founder of the Congregation taught, Priest Théodore Ratisbonne, is still an instrument for youth to acquire the necessary knowledge for the true human and Christian values. With the need to search for other approaches to address the P.E. classes of such institution, we chose as content to perform our intervention, the Adventure Activities, where we could consider the potentials of outdoor work, as well as its capacity to offer a new education manner to the children. Therefore, during 2008, physical education developed its classes, in the segment of kindergarten, based on adventure activities. Reinventing this activity took place in the sports court, using ropes to build several tree climbing stations, such as double rope crossing, crossing logs, crossing ropes, handrail balance, climbing with access ladder stations and tire ladder for lifting. The performance of such proposal was possible due to the motivation of the P.E. in taking the different contents to the students of this institution, by credit of the principal for the work and the school for having the infrastructure to carry out such practices. We deduced that the choice for content had great success, because we verified that activities supplied to the students more motivation during classes and contributed to the development of given capacities, skills and values. Therefore, adventure sports, when worked in P.E. classes of Colégio Sion, took the students to challenging situations that, with their performance, guided them to overcoming moments and elevated their self-esteem, which certainly contributes to the Christian, citizen and critical graduation of the student at Colégio Sion .